Enhancing antioxidant extraction efficiency from red dragon fruit peel by green approach using novel optimization technique - Le Thi Kim Loan; Le Thi Nhu Thao; Bui The Vinh; Chaiyut Mansamut; Ngo Van Tai (Current Research in Green and Sustainable Chemistry, 2025)
This study is the first application of a combined sonication and enzyme extraction technique as green technology to recover biological compounds from the peel of red-fleshed dragon fruit, utilizing Response Surface Methodology (RSM) and Artificial Neural Network-Genetic Algorithm (ANN-GA). The peel of dragon fruit had sonication pretreatment for 10–30 min (X1), followed by hydrolysis using 0.1 % Pectinex Ultra SP-L enzyme at temperatures ranging from 30 to 60 °C (X2) for a duration of 60–120 min (X3). The Box-Behnken design was employed to structure the experiment. The levels of polyphenol, betacyanin, and antioxidant activity in the extract were utilized to assess the efficacy of the extraction method. The research demonstrated a substantial enhancement in efficiency by the application of ultrasound pretreatment during the enzymatic hydrolysis of dragon fruit peel. The study identified the ideal parameters for the extraction process using the ANN-GA approach, which include an ultrasonic duration of 27.5 min, an enzyme incubation temperature of 47.1 °C, and an enzyme incubation duration of 135.1 min. Under these conditions, the extract exhibited a total phenolic content of 165.34 mg GAE/g peel weight, betacyanin content of 131.87 mg/100 g peel weight, and an antioxidant activity of 0.92 mg TE/100 g by using DPPH radical scavenging activity assay. The research demonstrated that dual treatment enhances the extraction process of chemicals from by-products, particularly dragon fruit peel. The study established a foundation for future research on the utilization and integration of effective extraction technologies to enhance the quality of extracts for use in the food sector.